INVESTASI REKSA DANA DENGAN SISTEM MUDHARABAH OLEH PT.BANK SYARIAH MANDIRI PEKALONGAN - Agus Maulana Ramdhono, A. Tulus Sartono, Muhyidin (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2012)
Mutual Fund is an organization that works for the small investor to take part in the investment world. Mutual Funds Sharia comes to meet the needs of investors to income derived from the investment of funds could be accounted for religious. Implementation of Shariah Fund has similarities to conventional mutual fund. The basic thing that distinguishes them among other application-contract agreement (engagement) Islam in its operational mechanism. Arrangements regarding the application of the agreement set forth in Sharia Fund DSN-MUI Fatwa No.20/DSNMUI/IV/2001. Under the decree, agreement occurring in Mutual Funds Sharia al-wakalah (representative) and mudaraba (profit sharing). Based on the description, the authors are interested in conducting a study entitled